ADMINISTRATIVE REFORM DI SEKTOR PEMERINTAHAN SEBAGAI PRA-KONDISI KEMUNCULAN AKTOR-AKTOR SOCIAL ENTREPRENEURSHIP (PENELAAHAN TERHADAP PENDEKATAN NEW PUBLIC MANAGEMENT) - Vandyarman Mulya Priyanda (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
Social entrepreneurship is a way to overcome problems that exist in the public domain. The involvement of social entrepreneurship actors in overcoming public problems will facilitate government work in providing services and solving public problems. However, social entrepreneurship actors will not emerge on their own. Ecosystems are needed that can support the emergence of social entrepreneurship in a country. At this point the role of the government becomes very important in terms of creating a good ecosystem for the development of social entrepreneurship. Therefore, the government must reform itself regarding administrative governance which will have implications for the creation of social entrepreneurship actors.